Effect of Different Tree Species on Physico-Chemical Properties of Soil under Rainfed Conditions of South-West Haryana - Asha; Yadav, P. K.; Kaushik, N.; Prakash, Ram; Jat, M. K.; Saroha, Diksha (Indian Forester, 2025)
The cultivation of tree species helps in nutrient cycling, microclimate regulation, green manure provision, and long-term land cover, which helps reduce soil erosion, particularly in arid and semi-arid regions. This study, conducted for the first time at the Regional Research Station, Bawal, Haryana, India, assessed the impact of three tree species (Pongamia pinnata, Prosopis cineraria and Ailanthus excelsa) on soil properties under rainfed conditions. Soil samples were collected from various depths (0-15, 15-30, 30-60, 60-90, 90-120, 120-150 and 150-180 cm) and analyzed for texture, pH, EC, organic carbon,CaCO3 content and leaf-litter nutrient status. Results showed that P. cineraria reduced soil pH (7.51), EC (0.19 dSm-1), and CaCO3 (0%) compared to the control (pH 8.3, EC 0.22 dSm-1, and 0.39% CaCO3), with these properties increasing with soil depth. Organic carbon content was significantly higher under the tree species (0.42% for P. cineraria, 0.41% for A. excelsa, and 0.33% for P. pinnata) compared to the control (0.19%). Leaf nutrient content, particularly NPK and micronutrients (except Mn), varied significantly among species, with P. cineraria showing the highest concentrations. The study highlights the potential of these tree species to improve soil quality and restore fertility through in situ manuring due to their high nutrient content.